RETHINKING ECONOMICS IN RESPONSE TO CURRENT CRISIS PHENOMENA - Przesławska, Gabriela (Ekonomia i Prawo. Economics and Law, 2016)
In seven years from the eruption of a global economic crisis, a noticeable change has taken place in the approach of economists, as well as international economic organisations (i.e. IMF and the World Bank), to analysing the occurring crisis phenomena. A purpose of the article is to present transformation of views and positions of the abovementioned communities in the context of experiences in overcoming crisis and of the modern challenges of post-crisis economy. In this scope, the article shows changes in economic theory and policy and proposals for the new state role, especially emphasizing the significance of institutional environment for socio-economic development. The assumed research task, performed on the basis of a critical analysis of subject’s literature, serves to verify an initial hypothesis of gradual formation of new rules of the game, i.e. institutional order, in the post-crisis world, of which Poland is a part. The postulated institutional order would constitute a connection of social, economic and political aspects. The analysis conducted in the article proved an influence of occurring crisis phenomena on evolution of economic science and policy. In this area, in order to increase explanatory and predictive power of macroeconomics, it is recommended to make use of a more heterodox approach which includes taking into account the financial markets’ behavior and macroeconomic effects of income inequalities. In general, it can be stated that current revaluations in thinking about economy, although being the prerequisites for institutional change, are not of a breakthrough character, so they do not constitute critical junctures in economic development and theory. In this regard, the significance of governments’ political will is emphasized as a basic factor in resolving problems resulting from global economic crisis.